Computer-aided image analysis for PD-L1 assessment in canine urothelial carcinoma - L.V. Muscatello; B. Bacci; E. Brigandì; C. Tugnoli; G. Avallone; P. Valenti; A. Giuliano; G. D’Annunzio; C. Benazzi; G. Sarli (The Veterinary Journal, 2026)

Tumour-associated macrophages in canine soft tissue sarcoma - G. Avallone; E. Brigandì; A. Rigillo; B. Bacci; P. Roccabianca (Journal of Comparative Pathology, 2025)

Description of spatial proliferation patterns in canine neoplasms - E. Brigandì; B. Bacci; B. Brunetti; A. Rigillo; P. Roccabianca; G. Bellini; C. Chiappelli; G. Avallone (Journal of Comparative Pathology, 2025)

Multiplex immunohistochemistry and supervised machine learning for immune cells topography in canine PDL1 tested urothelial Carcinoma - L. Muscatello; T. Franceschini; C. Tugnoli; A. Grillini; B. Bacci; G. Avallone; P. Valenti; M. Fiorentino; G. Sarli (Journal of Comparative Pathology, 2025)

Investigation of HER2 gene amplification and protein expression in canine primary pulmonary carcinoma - B. Brunetti; R. Marchetti; F. Millanta; G. Tura; L.V. Muscatello; E. Di Oto; E.L. Laddaga; A. De Leo; G. Tallini; B. Bacci (Journal of Comparative Pathology, 2023)

TP53 mutations in canine liposarcoma - D. De Biase; T. Maloberti; V. Pellegrino; B. Bacci; P. Roccabianca; E. Lepri; L. Crippa; G. Avallone (Journal of Comparative Pathology, 2023)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Lethal Effect and Behavioral Responses of Leaf-Cutting Ants to Essential Oil of Pogostemon cablin (Lamiaceae) and Its Nanoformulation - A G Rocha; B M S Oliveira; C R Melo; T S Sampaio; A F Blank; A D Lima; R S Nunes; A P A Araújo; P F Cristaldo; L Bacci (Neotropical Entomology, 2018)

Phylogenetic patterns of ant–fungus associations indicate that farming strategies, not only a superior fungal cultivar, explain the ecological success of leafcutter ants - Ulrich G. Mueller; Melissa R. Kardish; Heather D. Ishak; April M. Wright; Scott E. Solomon; Sofia M. Bruschi; Alexis L. Carlson; Maurício Bacci (Molecular Ecology, 2018)
To elucidate fungicultural specializations contributing to ecological dominance of leafcutter ants, we estimate the phylogeny of fungi cultivated by fungus‐growing (attine) ants, including fungal cultivars from (i) the entire leafcutter range from southern South America to southern North America, (ii) all higher‐attine ant lineages (leafcutting genera Atta , Acromyrmex ; nonleafcutting genera Trachymyrmex , Sericomyrmex ) and (iii) all lower‐attine lineages. Higher‐attine fungi form two clades, Clade‐A fungi ( Leucocoprinus gongylophorus , formerly Attamyces ) previously thought to be cultivated only by leafcutter ants, and a sister clade, Clade‐B fungi, previously thought to be cultivated only by Trachymyrmex and Sericomyrmex ants. Contradicting this traditional view, we find that (i) leafcutter ants are not specialized to cultivate only Clade‐A fungi because some leafcutter species ranging across South America cultivate Clade‐B fungi; (ii) Trachymyrmex ants are not specialized to cultivate only Clade‐B fungi because some Trachymyrmex species cultivate Clade‐A fungi and other Trachymyrmex species cultivate fungi known so far only from lower‐attine ants; (iii) in some locations, single higher‐attine ant species or closely related cryptic species cultivate both Clade‐A and Clade‐B fungi; and (iv) ant–fungus co‐evolution among higher‐attine mutualisms is therefore less specialized than previously thought. Sympatric leafcutter ants can be ecologically dominant when cultivating either Clade‐A or Clade‐B fungi, sustaining with either cultivar‐type huge nests that command large foraging territories; conversely, sympatric Trachymyrmex ants cultivating either Clade‐A or Clade‐B fungi can be locally abundant without achieving the ecological dominance of leafcutter ants. Ecological dominance of leafcutter ants therefore does not depend primarily on specialized fungiculture of L. gongylophorus (Clade‐A), but must derive from ant–fungus synergisms and unique ant adaptations.

Variation in the composition and activity of ants on defense of host plant Turnera subulata (Turneraceae): strong response to simulated herbivore attacks and to herbivore’s baits - Nayara G. Cruz; Paulo F. Cristaldo; Leandro Bacci; Camilla S. Almeida; Gabriela P. Camacho; Alisson S. Santana; Efrem J. M. Ribeiro; Alexandre P. Oliveira; Abraão A. Santos; Ana P. A. Araújo (Arthropod-Plant Interactions, 2018)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Long-term efficacy of microbiology-driven periodontal laser-assisted therapy - F. S. Martelli; E. Fanti; C. Rosati; M. Martelli; G. Bacci; M. L. Martelli; E. Medico (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Planting of fungus onto hibernating workers of the fungus-growing ant Mycetosoritis clorindae (Attini, Formicidae) - U. G. Mueller; A. Ortiz; M. Bacci (Insectes Sociaux, 2010)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

Molecular phylogeny and karyotype differentiation in Paratelmatobius and Scythrophrys (Anura, Leptodactylidae) - L. B. Lourenço; M. Bacci-Júnior; V. G. Martins; S. M. Recco-Pimentel; C. F. B. Haddad (Genetica, 2008)

Use of Immunomagnetic Separation Technique and Polymerase Chain Reaction for Detection of Verocytotoxin-Producing Escherichia coli in Cattle at Slaughter - S. Bonardi; C. Bacci; G. Pizzin; B. Orlandini; E. Donati; F. Brindani; E. Foni; C. Chiapponi; E. Aibino (Veterinary Research Communications, 2005)

Nesting biology of the fungus growing ants Mycetarotes Emery (Attini, Formicidae) - S. E. Solomon; U. G. Mueller; T. R. Schultz; C. R. Currie; S. L. Price; A. C. Oliveira da Silva-Pinhati; M. Bacci; H. L. Vasconcelos (Insectes Sociaux, 2004)

Alteration of Constitutive Heat Shock Protein 70 (HSC70) Production by in vitro Culture of Porcine Preimplanted Embryos - C. Bernardini; P. Fantinati; G. Castellani; M. Forni; A. Zannoni; E. Seren; M.L. Bacci (Veterinary Research Communications, 2003)

UV‐B radiation causes early ripening and reduction in size of fruits in two lines of tomato (Lycopersicon esculentum Mill.) - L. Bacci; D. Grifoni; F. Sabatini; G. Zipoli (Global Change Biology, 1999)
Summary An open‐air experiment was performed in Pistoia (Italy) to investigate the possible protective role played by different contents of UV‐B absorbing compounds to realistic UV‐B supplementation and to study its effect on plant fruit production. A mutant line and its normal counterpart of Lycopersicon esculentum Mill, which differ in the content of UV‐B absorbing compounds, were used. Additional UV‐B radiation in the field was supplied to simulate a 20% stratospheric ozone depletion. Two groups of plants were grown: ‘control’, where plants received only natural solar UV‐B radiation, and ‘UV‐B’ treatment, where plants were grown under supplemental UV‐B. The results of the experiment showed that the content of UV‐B absorbing compounds of treated plants did not differ from that of the control in both lines. This indicates that natural sunlight, in Mediterranean areas, is saturating for synthesis of these compounds also in plants with normal content of UV‐B absorbing compounds. Consequently, plants are not able to produce significant additional amounts of them, in response to a realistic UV‐B supplementation, in order to protect the plant from additional UV‐B radiation. No different responses to the UV‐B supplementation were found between the two lines. The most significant UV‐B effect was an earlier reddening of fruits in comparison with the ‘control’ accompanied by a reduction in the size of mature fruits. No significant effects of UV‐B treatment were observed in biomass accumulation, leaf ontogeny, flowering or productivity.

Location of the β-galactosidase of the yeast Kluyveromyces marxianus var. marxianus ATCC 10022 - M. Bacci Júnior; C. G. Siqueira; S. A. Antoniazi; J. Ueta (Antonie van Leeuwenhoek, 1996)